Pro .NET 4 Parallel Programming in C# - Freeman, Adam.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Parallel programming has been revolutionised in .NET 4, providing, for the first time, a standardised and simplified method for creating robust, scalable and reliable multi-threaded applications. The Parallel programming features of .NET 4 allow the programmer to create applications that harness the power of multi-core and multi-processor machines. Simpler to use and more powerful than (3z(Bclassic(3y (B.NET threads, parallel programming allows the developer to remain focused on the work an application needs to perform. In Pro .NET 4 Parallel Programming in C#, Adam Freeman presents expert advice that guides you through the process of creating concurrent C# applications from the ground up. You$1 (Bll be introduced to .NET$1 (Bs parallel programming features, both old and new, discover the key functionality that has been introduced in .NET 4, and learn how you can take advantage of the power of multi-core and multi-processor machines with ease. Pro .NET 4 Parallel Programming in C# is a reliable companion that will remain with you as you explore the parallel programming universe, elegantly and comprehensively explaining all aspects of parallel programming, guiding you around potential pitfalls and providing clear-cut solutions to the common problems that you will encounter.s
Introducing Parallel Programming -- Task Programming Hibernate -- Sharing Data -- Coordinating Tasks -- Parallel Loops -- Parallel LINQ -- Testing and Debugging -- Common Parallel Algorithms.
Keywords: Computer science; Computer Science; Computer Science, general